Design of a Walking Assistance Lower Limb Exoskeleton for Paraplegic Patients and Hardware Validation Using CoP. (11th February 2013) - Kim, Jung-Hoon; Han, Jeong Woo; Kim, Deog Young; Baek, Yoon Su
The design of an assistive lower limb exoskeleton robot for paraplegic patients that can measure the centre of pressure is presented. In contrast with most biped walking robots, the centre of pressure (CoP) or zero moment point (ZMP) has not been actively used in the operation of exoskeleton robots. In order to measure CoP in our exoskeleton robot, two kinds of force sensor units are installed in the exoskeleton: low profile force sensors in foot modules to measure the human weight transferred to the ground and a load cell at the shank frame to measure the supporting force. The CoP of the exoskeleton robot is calculated from the above force sensors, an inclinometer at the waist, and the positions of 14 DOF exoskeleton joints with an algorithm to change the fixed pivot using a foot contact sensor. Experiments on an able-bodied person wearing the designed exoskeleton and walking on the ground are performed to validate the designed hardware system. Through the experiments, the trajectory of the CoP of the exoskeleton with a wearer are calculated based on the proposed algorithm and it is compared with the value measured by a commercial pressure measurement system.